Dialogues with the absent other: using reported speech and the vocabulary of citizenship for contesting ecological laws and institutions - Castro, P.; Santos, T. R. (Discourse and Society, 2020)
This article examines how a professional group articulates views of the new laws and institutions that call them to accept new practices and new meaning in the name of the ecological common good. Drawing on a framework integrating the approach of social representations and rhetorical social psychology with legal institutionalism, we analyze in-depth interviews and focus groups (n = 29) with artisanal fishers. We explore how fishers use reported speech, that is, the quotation of others or self in own discourse, for building representations of Self, institutional-Others and their relations, examining also the values and dimensions of citizenship they mobilize with it. We show how fishers consistently use reported speech for presenting a negative institutional-Other acting in disrespect of the civil and political dimensions of citizenship, and a positive Self acting as a competent citizen – although rarely as a good ecological citizen. We discuss how focusing on reported speech by drawing on a theorization of how the institutional dimension interacts with the micro-level of interaction and discourse extends current comprehension of how contestation of the new meaning embedded in new laws can be warranted and maintained.